Skookum Root: Ethnobotany of Hellebore (Veratrum viride) in Northwest British Columbia - Armstrong, Chelsey Geralda (Ethnobiology Letters, 2018)
This research considers some of the uses and harvest protocols of one of the most important medicinal plants for Indigenous peoples throughout British Columbia, Vertarum viride (skookum root, green false hellebore, Indian poke, Indian hellebore). The medicinal qualities of V. viride are well respected given its equally powerful ability to paralyze and kill. Using botanical, ethnographic, ethnohistoric, and linguistic data, a broad overview of hellebore is provided for the northwest coast of North America, followed by an in-depth consideration of Gitxsan harvest protocol, witnessed through participant observation.